DC's Legends of tomorrow. The complete fifth season [videorecording (DVD)] - Berlanti, Greg; Guggenheim, Marc; Kreisberg, Andrew, 1971-; Klemmer, Phil (Warner Bros. Home Entertainment, 2020)
After season four, the Legends had to sacrifice one of their won. But in attempting to change her future, Zari accidentally changed not just the past she shared with Nate, but fundamentally changed who the Legends are in season five. Can our team go back to who they were this season? And can the Legends stop the literal hell that Astra has unleashed on the world?